Mouse RAD54 Affects DNA Double-Strand Break Repair and Sister Chromatid Exchange - Dronkert, Mies L. G. (American Society for Microbiology, 2000)
Cells can achieve error-free repair of DNA double-strand breaks (DSBs) by homologous recombination through gene conversion with or without crossover. In contrast, an alternative homology-dependent DSB repair pathway, single-strand annealing (SSA), results in deletions. In this study, we analyzed the effect of mRAD54, a gene involved in homologous recombination, on the repair of a site-specific I-SceI-induced DSB located in a repeated DNA sequence in the genome of mouse embryonic stem cells. We used six isogenic cell lines differing solely in the orientation of the repeats. The combination of the three recombination-test substrates used discriminated among SSA, intrachromatid gene conversion, and sister chromatid gene conversion. DSB repair was most efficient for the substrate that allowed recovery of SSA events. Gene conversion with crossover, indistinguishable from long tract gene conversion, preferentially involved the sister chromatid rather than the repeat on the same chromatid. Comparing DSB repair in mRAD54 wild-type and knockout cells revealed direct evidence for a role of mRAD54 in DSB repair. The substrate measuring SSA showed an increased efficiency of DSB repair in the absence of mRAD54. The substrate measuring sister chromatid gene conversion showed a decrease in gene conversion with and without crossover. Consistent with this observation, DNA damage-induced sister chromatid exchange was reduced in mRAD54-deficient cells. Our results suggest that mRAD54 promotes gene conversion with predominant use of the sister chromatid as the repair template at the expense of error-prone SSA.